2011
DOI: 10.1172/jci43802
|View full text |Cite
|
Sign up to set email alerts
|

Suppressed monocyte recruitment drives macrophage removal from atherosclerotic plaques of Apoe–/– mice during disease regression

Abstract: Experimental models of atherosclerosis suggest that recruitment of monocytes into plaques drives the progression of this chronic inflammatory condition. Cholesterol-lowering therapy leads to plaque stabilization or regression in human atherosclerosis, characterized by reduced macrophage content, but the mechanisms that underlie this reduction are incompletely understood. Mice lacking the gene Apoe (Apoe -/-mice) have high levels of cholesterol and spontaneously develop atherosclerotic lesions. Here, we treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
317
4
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 306 publications
(347 citation statements)
references
References 66 publications
21
317
4
1
Order By: Relevance
“…In conclusion, the data clearly identify IL-17A as an independent and effective proinflammatory modulator in human plaque microenvironment that may promote plaque instability and plaque rupture; however, further studies are necessary to evaluate the relevance of the findings in the clinical setting. Because IL-17A is prominently involved in early and advanced atherosclerotic lesion formations, we further evaluated the underlying mechanisms by analyzing the impact of IL-17A on monocytes and monocyte-derived cells, which are known to play a major role during disease development and progression (4,33,34). Previous studies have convincingly shown that migratory egress of monocyte-derived cells is a major step (35), but reduction of monocyte recruitment seems to be even more important in reducing plaque monocyte-originated cells burden (4).…”
Section: Synergistic Effects Of Il-17a In Addition To Lps In the Plaqmentioning
confidence: 99%
See 2 more Smart Citations
“…In conclusion, the data clearly identify IL-17A as an independent and effective proinflammatory modulator in human plaque microenvironment that may promote plaque instability and plaque rupture; however, further studies are necessary to evaluate the relevance of the findings in the clinical setting. Because IL-17A is prominently involved in early and advanced atherosclerotic lesion formations, we further evaluated the underlying mechanisms by analyzing the impact of IL-17A on monocytes and monocyte-derived cells, which are known to play a major role during disease development and progression (4,33,34). Previous studies have convincingly shown that migratory egress of monocyte-derived cells is a major step (35), but reduction of monocyte recruitment seems to be even more important in reducing plaque monocyte-originated cells burden (4).…”
Section: Synergistic Effects Of Il-17a In Addition To Lps In the Plaqmentioning
confidence: 99%
“…Because IL-17A is prominently involved in early and advanced atherosclerotic lesion formations, we further evaluated the underlying mechanisms by analyzing the impact of IL-17A on monocytes and monocyte-derived cells, which are known to play a major role during disease development and progression (4,33,34). Previous studies have convincingly shown that migratory egress of monocyte-derived cells is a major step (35), but reduction of monocyte recruitment seems to be even more important in reducing plaque monocyte-originated cells burden (4). We already showed that IL-17A inhibition reduces lesional chemokine expression (CCL5) in early atherosclerotic lesions and IL-17A induces expression of adhesion molecules on endothelial cells (VCAM-1) (5, 7).…”
Section: Synergistic Effects Of Il-17a In Addition To Lps In the Plaqmentioning
confidence: 99%
See 1 more Smart Citation
“…This process causes the macrophages to transform into lipid-laden macrophage foam cells which can no longer escape the arterial wall (Potteaux et al 2011). The excessive cellular cholesterol in macrophage foam cells can be efficiently removed by the potent cholesterol acceptors lipid-free apoA-I and HDLs to be transported back to the liver by a process termed reverse cholesterol transport.…”
Section: Macrophage Cholesterol Efflux and Reverse Cholesterol Transportmentioning
confidence: 99%
“…New data also suggest that normalization of cholesterol can correct monocyte recruitment into the aorta and additionally, lead to decreased M content in atherosclerotic aortas. Treatment of Apoe -/-with apoE-encoding adenoviral vectors induced plaque regression, and attenuated CCR7-independent aortic M content (Potteaux et al, 2011). Thus, interfering with monocyte recruitment into and possible egress from atherosclerotic plaques may be therapeutically beneficial, in parallel with aggressive lipid lowering therapies, to maintain and reinforce the reduction in monocyte recruitment to the aorta.…”
Section: Egress Of Macrophages and Dendritic Cells From Atherosclerotmentioning
confidence: 99%